2021
DOI: 10.1055/s-0041-1730996
|View full text |Cite
|
Sign up to set email alerts
|

Augmentative and Alternative Communication Supports for Language and Literacy in Preschool: Considerations for Down Syndrome and Autism Spectrum Disorder

Abstract: Children with Down syndrome and children with autism spectrum disorder have a range of speech abilities during preschool that impacts access to both language and literacy instruction. It is the responsibility of the speech-language pathologist to advocate for and provide intervention using augmentative and alternative communication (AAC) through individualized assessment. This article provides a review of the literature supporting the use of AAC during preschool for both language and literacy development in ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
(70 reference statements)
0
1
0
Order By: Relevance
“…In a case study, Iacono and Duncum (1995) found that the use of speech output AAC technology paired with manual signs was more effective than manual signs alone for eliciting single-word productions as well as two- and three-word combinations. In recent years, SGDs have been increasingly used with children with developmental disabilities to support communication development during early intervention and preschool ( Romski et al, 2015 ; Barton-Hulsey et al, 2021 ). The outcomes of this work suggest positive gains in receptive and expressive communication for children with developmental disabilities.…”
Section: Introductionmentioning
confidence: 99%
“…In a case study, Iacono and Duncum (1995) found that the use of speech output AAC technology paired with manual signs was more effective than manual signs alone for eliciting single-word productions as well as two- and three-word combinations. In recent years, SGDs have been increasingly used with children with developmental disabilities to support communication development during early intervention and preschool ( Romski et al, 2015 ; Barton-Hulsey et al, 2021 ). The outcomes of this work suggest positive gains in receptive and expressive communication for children with developmental disabilities.…”
Section: Introductionmentioning
confidence: 99%